Synthesis of Diads and Triads Derived from Carotenoids and Fullerene C60 - Devens Gust; Thomas A. Moore; Ana Moore; E. N. Durantini (Molecules, 2000)
A convenient procedure for the synthesis of supramolecules bearing carotenoids and fullerene C60 is reported. The amphipathic nature and the high yield of charge separation of these compounds make them candidates in the formation of transmembrane charge gradients.